Tackling the illegal trade of endangered plants, interview data 2018-2020 - Lavorgna, Anita (UK Data Service, 2020)
In the context of the "FloraGuard" project, we conducted interviews interested in the characteristics of the illegal wildlife (plant) market, actors involved, policing and plant recovery strategies in United Kingdom, and from a transnational perspective. Illegal commerce in plants and their derivatives threatens and destroys numerous species and important natural resources, and may cause phytosanitary and health problems. This illegal trade, which has been boosted by the commercialisation of the internet, has been relatively overlooked in criminology research. Furthermore, the policing of illegal plant markets remains limited and poorly resourced, with law enforcement agencies lacking awareness and technical capacity in investigation and prosecution services. Over the last 60 years, commerce in exotic wild plants increased in Western countries (Sajeva et al 2007). Alongside the legal trade in plants, the profitability of the market also boosted illegal markets. Wild plant crimes have long been a focus of concern mainly in conservation science. In criminology, while the illegal trade in wild animals (and animal parts eg ivory) is receiving increasing attention, the illegal trade in plants has so far been under-investigated. However, wild plant trafficking threatens and destroys numerous species and important natural resources (Herbig & Joubert 2006) and hinders the rule of law and security as profits are also used to finance other forms of trafficking (WWF 2016). The Internet has increased the illegal trade in wild plants, facilitating the encounter of supply and demand; no matter how highly specialised the market in certain wild plants, it is much easier to find potential buyers or sellers online than in the physical world (Lavorgna 2014a). There is consensus that the policing of such a criminal activity is still scarce and poorly resourced (Nurse 2011; Elliot 2012; Lavorgna 2014a; Lemieux 2014; Runhovde 2016). A major challenge is the fact that law enforcement agencies have limited training opportunities and lack of equipment and specific expertise to counter effectively this illegal trade (CITES2016). In this context, the question of how can we best control and prevent this criminal market needs to be addressed. The proposed project combines innovative and cross-disciplinary ways of analysing online marketplaces for the illegal trade in endangered plants and analyses of existing policing practices to assist law enforcement in the detection and investigation of illegal trades of endangered plants. It focuses on the UK, which serves as a major transit and destination market for the European region (EU Commission2016). The result of this research will be of significant importance for the work of law enforcement (eg national wildlife crime units, custom officers) in combating the illegal trade in endangered plants (in both its online and offline elements), disrupt criminal networks involved in such trade, and preserve biodiversity. In line with the latest WWF position paper (WWF 2016), the project fosters the improvement of awareness and technical capacity in investigation and prosecution services for wildlife crimes. The proposed approach will identify and disseminate best practice for other researchers and law enforcement officers with an interest in online crime markets and wildlife policing; in addition, it will improve our understanding of the online marketplaces and the offline market routes for the trafficking of endangered plants into Western countries, supporting new avenues of investigation. By integrating insights and expertise from criminology, computer sciences and conservation science, the proposed project has also important implications for demonstrating interdisciplinary methodological developments. The research is structured around three cumulative work-packages (WP). WP1 comprises analysis of economic, social and geographical dynamics of a sample of online marketplaces active in the UK and associated with the illegal trade of endangered plants. WP2 focuses on the policing of this criminal activity by mapping current law enforcement practices and interventions, assessing their effectiveness in the light of the findings of WP1, and identifying law enforcement's needs for more effective policing. WP3 develops and tests a digital package of resources to assist law enforcement investigations into illegal trades of endangered plants in the UK. In doing so, it promotes engagement and effective communication with a non-academic audience (law enforcement, NGOs, botanic gardens, international institutions). The Royal Botanic Garden (Kew, the scientific authority for CITES plant trade in the UK) and the UK Border Force are formal non-academic partners to this project.